The Principle of Justice in Unilateral Termination of Employment: A Critical Legal Analysis of the Job Creation Law - Ahmad Baqi; Aicha Azdina Adly Fesya (ISNU Nine-Star Multidisciplinary Journal, 2025)
Unilateral termination of employment (PHK) has become a crucial issue in the dynamics of the Indonesian labor market, particularly following the enactment of Law Number 11 of 2020 concerning Job Creation. This study aims to analyze the principle of justice in the practice of unilateral layoffs through a critical legal approach. This approach is used to examine whether the provisions of the Job Creation Law reflect substantive justice for workers or actually strengthen the dominance of employer interests. The research method used is normative juridical with a statutory and conceptual approach, and qualitative analysis. The results show that although the Job Creation Law claims to provide flexibility in industrial relations, in practice it has the potential to weaken legal protection for workers experiencing unilateral layoffs. Therefore, a more balanced policy formulation is needed so that the principle of justice can truly be realized in the employment relationship between employers and employees.